Homologous recombination deficiency in ovarian cancer: a review of its epidemiology and management - onadi, Renata Rodrigues da Cunha Colombo (2019)
Ovarian cancer patients with homologous recombination deficiencies exhibit specific clinical behaviors, and improved responses to treatments, such as platinum-based chemotherapy and poly (ADP-ribose) polymerase (PARP) inhibitors, have been observed. Germline mutations in the BRCA 1/2 genes are the most well-known mechanisms of homologous recombination deficiency. However, other mechanisms, such as germline and somatic mutations in other homologous recombination genes and epigenetic modifications, have also been implicated in homologous recombination deficiency. The epidemiology and implications of these other mechanisms need to be better understood to improve the treatment strategies for these patients. Furthermore, an evaluation of various diagnostic tests to investigate homologous recombination deficiency is essential. Comprehension of the role of homologous recombination deficiency in ovarian cancer also allows the development of therapeutic combinations that can improve the efficacy of treatment. In this review, we discuss the epidemiology and management of homologous recombination deficiency in ovarian cancer patients.